Particularities of the changes in young swimmers` body adaptation to the stimuli of physical and mental stress in sports training process - Mihailescu, L.; Dubit, N.; Mihailescu, L. E.; Potop, V. (PeerJ, 2021)
Background: A factor favoring the swimming performance increase is the adaptation and readaptation of body energetic and functional systems to the physical and mental stress stimuli in training and competitions. The efficiency of monitoring the young swimmers` training is based on a precise determination of the changes in the specific adaptations. The evaluation and control of the biochemical, mental and motor changes ensure the knowledge of the particularities of body adaptation in different training stages. Methods: Six young swimmers aged 12-16 years specialized in 100 m event participated in this study, conducted in four stages (E1-general, E2-specific, E3-pre-competitive and E4-competitive). The distress occurrence during adaptation to training and competition stimuli was studied in 3 levels: mental (Cohen & Williamson Test (CWT), Cohen Perceived Stress Test (CPST), Competition Anxiety Test (SCAT), Craciun Test (CT)), motor (workouts monitoring, planning of means on training areas, anaerobic threshold assessment and average training speed calculation) and biochemical (blood lactate (La) and blood glucose (Glu) before and after effort—5 and 15 minutes; level of metabolic biochemical parameters, lymphocytes and blood glucose, and also hormonal parameters—norepinephrine, prolactin and cortisol—before and after competition effort). Results: Quantity results of the mental, motor and biochemical tests were analyzed in groups; the quality results for each subject in dynamics were analyzed by comparison and correlation. Psychological tests showed increases in athletes` mental behavior by 34% at CWT (p < 0.05), by 37.5% at CPST (p < 0.05), average stress level at SCAT and 70% stress in self-confidence at CT (p < 0.01). Biochemical tests revealed an ascending dynamics of La accumulated after specific effort, with peaks in E2 period (p < 0.05) and decreases in E3 compared to E2 (p < 0.05), revealing the adaptation to specific effort and the increase in anaerobic capacity. The Glu values decrease in pre-effort and increase in minute 5 and 15 post-effort (p < 0.05) in E2 and decrease in pre- and post- effort in E3 (p < 0.05), showing the effort impact on body and ability to recover after effort. Athletes` individual metabolic results were 50% above maximum values, mainly post-effort (42%); hormonal results were 17% over maximum values, mainly post-effort (14%). Spearman`s correlative analysis of the induced-stress stimuli in workouts revealed 6.06% significant correlations at p < 0.05 and 9.1% strong connections in competitions: 4.67% significant correlations at p < 0.05 and 6.4% strong connections. Conclusion: The research demonstrated that the mental and biochemical tests results correlation with the specific motor tests facilitated the correct individualization of effort orientation in training and recovery and contributed to the knowledge of the particularities of young swimmers` body adaptation to training and competition effort.